A basis for regional competitiveness: socio-economic potential - Borovitskaya, Marina V.; Strelnikov, Evgeniy V.; Khayrullina, Rezeda G.; Kolesnikov, Mikhail A.; Mukhniuk, Mariia I. (Revista de la Universidad del Zulia, 2020)
Regional strategic competitiveness management is a process of making strategic decisions on choosing alternatives, formed by comparing the existing potential of a particular region with the opportunities and threats of its external environment, as well as with global changes in the external environment. Its essence is manifested in the formation and implementation of the modern concept of highly efficient management on an innovative basis, corrected by constant monitoring of internal and external changes, assessment of the main parameters of the functioning and development of the region. The article describes the relevance and need to increase the competitiveness and attractiveness of the regions in order to create a favorable socio-economic climate for entrepreneurs, investors, residents, temporarily arriving and gaining advantages both in the domestic and foreign markets. Based on the study of the theoretical aspects of competitiveness, the basic elements of the region’s competitiveness are established, the features of the formation of the region’s competitive advantage at different stages of economic development and the factors influencing it are investigated. It is concluded that increasing the competitiveness of the region implies the need to create an integrated mechanism for managing the socio-economic, intellectual, natural potential of the region, which is supported by state programs both at the local and federal levels.